The transdiagnostic process of perfectionism - Egan, Sarah; Wade, T.; Shafran, R. (Asociación Española de Psicología Clínica y Psicopatología, 2012)
The transdiagnostic approach to theory and treatment of psychological disorders is gaining increasing interest. A transdiagnostic process is one that occurs across disorders and explains their onset or maintenance. The purpose of this review is to provide evidence that perfectionism is a transdiagnostic process that it is elevated in anxiety disorders, eating disorders, depression, obsessive compulsive personality disorder and somatoform disorders. Data are also reviewed to show that perfectionism can explain aetiology as it is a prospective predictor of depression and eating disorders. Perfectionism is also demonstrated to predict poorer outcome to treatment for anxiety disorders, eating disorders and depression, suggesting the need for specific treatment of perfectionism. Evidence is provided to demonstrate that perfectionism can be successfully treated with cognitive behavioural therapy which results in reduction in psychopathologies. Clinical guidelines are outlined to assist in treatment planning for individuals with elevated perfectionism.